NK1.1 receptor ligation or tumour interactions prime NK cells for IL2-mediated metabolic and functional responses - KEDIA MEHTA, NIDHI (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Natural Killer (NK) cells undergo a distinct metabolic response following cytokine stimulation, which involves increased rates of glycolysis and oxidative phosphorylation (OxPhos). This metabolic response is essential for NK cell function and involves key metabolic regulators including mTORC1, cMyc and Srebp. A key role for NK cells is recognizing and killing tumor and virally infected cells, which involves specific ligands on the target cells and NK cell activating receptors. Whether metabolic changes are required for the function of receptor-stimulated NK cells is not known. Here we show that activating NK cells in vitro through the activating receptor NK1.1 resulted in increased rates of glycolysis and OxPhos, though the observed increases were modest compared to the metabolic responses seen in cytokine stimulated NK cells. Of note, NK1.1 receptor ligation resulted in high levels of CD25 expression (the high affinity IL2 receptor subunit). Therefore we hypothesized that NK1.1 receptor ligation might prime NK cells to be more responsive to the T cell derived cytokine IL2. Indeed, stimulation of NK cells with NK1.1 plus IL2 resulted in robust metabolic outputs, high rates of both glycolysis and OxPhos, which were significantly higher than what was observed with either stimulus alone. This metabolic response was required for NK cell functional outputs, including IFN-γ production and cytotoxicity, and was dependent on mTORC1, cMyc and Srebp signaling. Furthermore, stimulating NK cell receptor signaling by co-culturing them with B16 melanoma cells also induced CD25 expression on a subset of NK cells that interacted with tumour cells. As predicted, addition of IL2 induced metabolic and functional responses in these CD25high cells that were dependent on mTORC1 and cMyc. These data suggest that interactions with target cells primes NK cells to respond to the T cell derived cytokine IL2 leading to robust metabolic and functional responses that facilitate prolonged NK cell responses in parallel with the adaptive immune response.
APPROVED
Keywords: Immunometabolism; NK1.1; NK cells; cMyc; mTORC1; CIML